Management of waste of stone processing in the framework of Euro integration of Ukraine - Shamrai, V. I.; Korobiіchuk, Vanentyn Vatslavovych; Sobolevskyi, Ruslan Vadymovych (Вісник ЖДТУ. Серія "Технічні науки", 2017)
Modern state of the stone industry in Ukraine undergoes drastic changes. In connection with the European integration of Ukraine, except for the requirements to product quality, the problem of proper waste management towards rock excavation and stone dressing enterprises occurs. The article studies the legislation of Ukraine and EU concerning waste. Major obstacles that arise on the way toward sustainable waste management of rock excavation and stone dressing production in Ukraine are identified. Also the benefits of correct waste management of the stone industry are determined. The strategy of waste management of rock excavation and stone dressing production is offered. It includes 3 stages: 1) waste prevention; 2) plan development of the enterprises toward waste management; 3) determination of the processing waste operations. On the basis of the legislation of the EU «Circular economy» the structure of the waste management plan of stone production is offered, and includes 4 main points for the rock excavation and stone dressing enterprises.